Mixed logit approach to modelling arrival time choice behaviour of cemetery and columbarium visitors during grave-sweeping festivals. Issue 4 (20th April 2016) - Szeto, W. Y.; Wong, R. C. P.; Yeung, Jonathan; Wong, S. C.
Abstract : Special events attract extraordinarily high travel demands over a relatively short time. Managing the travel demand for special events is more difficult than for normal commuting trips. Grave-sweeping is a special event that is popular in Asia, especially in Chinese societies. In Hong Kong, many people visit cemeteries and columbaria around the two traditional festivals, causing overcrowding at the sites and congestion on the access roads. To mitigate the adverse traffic effects, the police usually implement temporary traffic management measures to control the number of visitors accessing the sites. However, these measures often ignore visitors' arrival time preferences and hence their effectiveness is questionable. This study models and analyses the arrival time preferences of cemetery and columbarium visitors under various transport mode scenarios. The model development is based on 3128 choice decisions collected from 782 respondents. A mixed logit model is calibrated to investigate the potential taste heterogeneity of the respondents, and a likelihood ratio test demonstrates that the model is superior to a standard multinomial logit model and provides a better fit to the survey data. The model results indicate that in-vehicle travel time, total waiting and walking time, and the provision and travel fare of feeder services are significant factors influencing cemetery and columbarium visitors' arrival time choices. The effects of socio-economic factors are also examined and discussed. Based on the model results, recommendations are provided for managing the travel demand to cemeteries and columbaria at peak and off-peak hours on or around festival days.